Mumbai's aftermath : can India, Pakistan close ranks? - C. Raja Mohan (2009)
After the terror attacks in Mumbai, nuclear neighbours India and Pakistan have shown significant restraint amidst widespread fears of a military escalation. Their ability to avoid a conflict, however, depends on the uncertain prospects for concrete bilateral cooperation against terrorist groups.